Problems of Parole Application in Lithuania - MICHAILOVIČ, ILONA; JARUTIENĖ, LIUBOVĖ (Kriminologijos studijos, 2017)
Although parole is promoted by international recommendations, by the Penal Enforcement Law of Lithuania, by the Probation Law of Lithuania and by many criminal justice professionals, the application of parole decreases in Lithuanian case law. Jurisprudence parole cases show that in considering parole cases, court decisions are often based on very different criteria, and in some cases the same criteria are interpreted differently. Furthermore, despite more favorable opportunities to evaluate the criminal behavior risk of the convict reaching parole, the courts still tend to rely on slightly different criteria characterizing the convict. What is more, although parole legislation is becoming more liberal, according with the statistics, the recent percentage of paroled persons has been decreasing. Considering recent tendencies of parole application, it is unclear what factors may influence the existing differences of court practice, motives of parole application or declination and the relatively small number of paroled persons. In order to answer these questions, the authors of this study decided to examine the problems of parole application from several different perspectives. Authors conveyed a study that aimed at analyzing the work of parole boards and factors, which influence their parole decisions. Also, during this study, authors examined the peculiarities of judge parole decision-making. The study was intended to cover a wide range of factors that may influence parole application, so the authors did not limit the study to the court practice, but instead looked at the peculiarities of particular parole stages. During the empirical qualitative research, 7 interviews with judges and 8 interviews with the parole board members were performed, in accordance with the principle of the saturation of data. The research results should help both theorists and practitioners see parole from the point of view of judges and the parole board members; they should encourage dialogue as well as collaboration among judges that make decisions, the employees of penitentiary institutions and representatives of the public. In addition, the results should help to discover constructive ways of solving current parole problems and provide recommendations concerning a more fluent way of applying this institute.